Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

β1 and β3 subunits amplify mechanosensitivity of the cardiac voltage-gated sodium channel Nav1.5 - Maroni, Michele; Körner, Jannis; Schüttler, Jürgen; Winner, Beate; Lampert, Angelika; Eberhardt, Esther (Pflügers Archiv: European Journal of Physiology, 2019)
In cardiomyocytes, electrical activity is coupled to cellular contraction, thus exposing all proteins expressed in the sarcolemma to mechanical stress. The voltage-gated sodium channel Nav1.5 is the main contributor to the rising phase of the action potential in the heart. There is growing evidence that gating and kinetics of Nav1.5 are modulated by mechanical forces and pathogenic variants that affect mechanosensitivity have been linked to arrhythmias. Recently, the sodium channel β1 subunit has been described to stabilise gating against mechanical stress of Nav1.7 expressed in neurons. Here, we tested the effect of β1 and β3 subunits on mechanosensitivity of the cardiac Nav1.5. β1 amplifies stress-induced shifts of V1/2 of steady-state fast inactivation to hyperpolarised potentials (ΔV1/2: 6.2 mV without and 10.7 mV with β1 co-expression). β3, on the other hand, almost doubles stress-induced speeding of time to sodium current transient peak (Δtime to peak at − 30 mV: 0.19 ms without and 0.37 ms with β3 co-expression). Our findings may indicate that in cardiomyocytes, the interdependence of electrical activity and contraction is used as a means of fine tuning cardiac sodium channel function, allowing quicker but more strongly inactivating sodium currents under conditions of increased mechanical stress. This regulation may help to shorten action potential duration during tachycardia, to prevent re-entry phenomena and thus arrhythmias.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Cardiac ion channel; Mechanosensitivity; Patch-clamp; Sodium channel